Sex and gender in biomedicine theories, methodologies, results - Klinge, Ineke; Wiesemann, Claudia (Universitätsverlag Göttingen, 2010)
Sex and gender in biomedicine are innovative research concepts of theoretical and clinical medicine that enable a better understanding of health and disease, evidence-based knowledge, effective therapies, and better health outcomes for women and men. Gender Medicine stimulates new ways of doing research: that is to consider sex and gender at all levels of research, from basic research into gene polymorphisms to health behaviour. New research questions have been put forward that focus not on differences per se but on the development of differences. In this book, contributions from the field of neuroscience, addiction research, and organ transplantation exemplify concepts, approaches, methods and results in the field.